Knowledge hubs in times of crisis: the economic and strategic role of universities in international resilience networks - Литвинов, Олексій; Шевченко, Ірина (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2025)
This article explores the role of universities in frontline regions as strategic knowledge hubs contributing to international resilience networks amid wartime conditions. Using the case of the National Aerospace University “Kharkiv Aviation Institute” (KhAI), the study analyzes the modernization of educational content and internal quality assurance systems as tools of institutional resilience and economic sustainability. The authors present an integrated model that combines ESG standards, national accreditation requirements, and internal digital innovations to support educational continuity under crisis. The paper highlights the significance of hybrid learning, the creation of safe academic environments, stakeholder involvement, and academic integrity in transforming universities into centers of regional stability and global integration. The findings suggest that KhAI’s model can serve as a blueprint for higher education institutions operating in crisis-affected areas, supporting national human capital recovery and international cooperation in the field of education.  The scientific novelty of the study lies in introducing the concept of an "educational-regional trajectory" as an innovative approach to preserving knowledge hubs in frontline regions, as well as in developing the model of "safe education", which combines the use of shelters as learning spaces with hybrid formats and digital quality monitoring systems. This makes it possible to consider the KhAI experience not only as a local case, but as a universal model for modernizing higher education under wartime challenges. The practical significance of the study is defined by the applicability of its results to the activities of higher education institutions in Ukraine and includes the following aspects:  the proposed practices can be adapted and implemented to ensure the continuity of education under threat;  the results may serve as a basis for developing regional education development programs aimed at enhancing the resilience of educational environments and preserving human capital; the outlined approaches to modernizing educational content and internal quality assurance can form the foundation for further research on educational innovation, risk management, and educational recovery strategies;  the outcomes of this study serve as a strong argument in favor of supporting Ukrainian universities, which continue to demonstrate resilience and innovation despite the war.

У статті досліджується роль університетів прифронтових регіонів як стратегічних центрів знань, що сприяють формуванню міжнародних мереж стійкості в умовах воєнного стану. На прикладі Національного аерокосмічного університету «Харківський авіаційний інститут» (ХАІ) проаналізовано процес модернізації змісту освіти та внутрішньої системи забезпечення якості як інструментів інституційної стійкості та економічної життєздатності. Представлено інтегровану модель, що поєднує стандарти ESG, національні вимоги до акредитації та внутрішні цифрові інновації для забезпечення безперервності освітнього процесу в умовах кризи. Наголошено на важливості гібридного навчання, створення безпечного освітнього середовища, залучення стейкхолдерів і підтримання академічної доброчесності у перетворенні університетів на осередки регіональної стабільності та глобальної інтеграції. Доведено, що модель ХАІ може слугувати орієнтиром для закладів вищої освіти, які функціонують в умовах кризи, сприяючи відновленню людського капіталу та міжнародному співробітництву у сфері освіти. Наукова новизна роботи полягає у введенні концепту «освітньо-регіональної траєкторії» як інноваційного підходу до збереження центрів знань у прифронтових регіонах, а також у розробці моделі «безпечної освіти», що поєднує використання укриттів як навчальних просторів із гібридними форматами та цифровими системами моніторингу якості. Саме це дозволяє розглядати досвід ХАІ не лише як локальний кейс, а як універсальну модель модернізації вищої освіти в умовах воєнних викликів. Практична значущість результатів роботи визначається можливістю їх застосування у діяльності закладів вищої освіти України та полягає у наступному: запропоновані практики можуть бути адаптовані й впроваджені для збереження освітнього процесу в умовах загроз; результати можуть слугувати основою для розробки регіональних програм розвитку освіти, спрямованих на підвищення стійкості освітнього середовища та збереження людського капіталу; окреслені підходи до модернізації змісту освіти та внутрішнього забезпечення якості можуть стати підґрунтям для подальших досліджень з питань інновацій в освіті, управління ризиками та формування стратегій освітнього відновлення; напрацювання роботи є аргументом на користь підтримки українських університетів, які, незважаючи на війну, демонструють стійкість та інноваційність.
Університети як центри знань у кризовий період: економічна та стратегічна роль вищої освіти у міжнародних мережах стійкості
Keywords: education modernization; resilience; frontline universities; quality assurance system; hybrid learning; digitalization; academic integrity; international cooperation; модернізація освіти; стійкість; університет прифронтового регіону; система забезпечення якості; гібридне навчання; цифровізація; академічна доброчесність; міжнародне співробітництво